2010
DOI: 10.1002/pssa.200925393
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐optical and cathodoluminescence properties of low temperature grown ZnO nanorods/p‐GaN white light emitting diodes

Abstract: Vertically aligned ZnO nanorods (NRs) with a diameter in the range of 160–200 nm were grown on p‐GaN/sapphire substrates by aqueous chemical growth technique and white light emitting diodes (LEDs) are fabricated. The properties of this LED were investigated by parameter analyzer, cathodoluminescnce (CL), electroluminescence (EL), and photoluminescence (PL). The I–V characteristics of the fabricated ZnO/GaN heterojunction revealed rectifying behavior and the LED emits visible EL when bias is applied. From the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…The physical origin of the electroluminescence has been extensively studied but is still under debate [373][374][375]. There has also been a controversy about whether the emission is from the n-ZnO side [147,376] or the p-GaN side [372,377].…”
Section: Inorganic Heterojunction Ledsmentioning
confidence: 99%
“…The physical origin of the electroluminescence has been extensively studied but is still under debate [373][374][375]. There has also been a controversy about whether the emission is from the n-ZnO side [147,376] or the p-GaN side [372,377].…”
Section: Inorganic Heterojunction Ledsmentioning
confidence: 99%
“…The round-shaped spot is originated from the whole disk-shaped ZnO nanowires layer. Most previous works exhibited a strong EL emission from forward bias beyond 10 V at higher wavelength [148][149][150][151][152]. Another study showed different EL behavior from other nZnO/p-GaN heterojunctions where the EL generated only from either the n-ZnO or p-GaN side [143].…”
Section: Hybrid / Heterostructuresmentioning
confidence: 93%
“…These properties include direct and wide band gap, large excitons binding energy and deep level defect emission [1,8,44,45]. As direct band gap is good for short wavelength photonics, high excitons binding energy permits effective excitonic emission at ambient temperature [46] and deep level defect emission is responsible for covering the whole visible region beside ultra violet emission [1,8,46,47].…”
Section: Optical Propertiesmentioning
confidence: 99%